Ibn-e- Arabi - Abu Javed Niyazi (Karachi, 2000)
"Ibn-e-Arabi, a celebrated Andalusian Sufi mystic and philosopher, is renowned for his teachings on unity of existence (Wahdat al-Wujud) and spiritual metaphysics."